Manajemen Fundrising Melalui Aplikasi Crowdfunding (Studi Kasus Pada Yayasan Hubbul Wathon Kebumen) - Nur Iman Hakim Al Faqih; Vima Faradilah; Umu Habibah; Irvan Fardani; Moh. Agung Saputro (Fakultas Ekonomi dan Bisnis Islam IAINU Kebumen, 2021)
The development of technology is a necessity that has an impact on changing perspectives in various aspects of life. The demand for adjustment to the times has become a necessity to maintain the existence of the ongoing life. Likewise with philanthropy, although the purpose of philanthropic activities is non-profit activities, they must keep up with the times. One that is applied in philanthropic activities is fundrising through the crowdfunding application. One of the institutions that apply this crowdfunding system is the Hubbul Watton Kebumen Foundation. Based on the analysis results, the fundring management at the Foundation has applied good management functions, in terms of planning, organizing, distributing work and controlling it. This crowdfunding system has the advantage that it has a very broad reach because the system used is web-based which can be accessed by anyone.